Citrulline stimulates muscle protein synthesis, by reallocating ATP consumption to muscle protein synthesis. Issue 4 (8th May 2019) - Goron, Arthur; Lamarche, Frédéric; Blanchet, Sandrine; Delangle, Pascale; Schlattner, Uwe; Fontaine, Eric; Moinard, Christophe
Abstract: Background: Animal studies and clinical data support the interest of citrulline as a promising therapeutic for sarcopenia. Citrulline is known to stimulate muscle protein synthesis, but how it affects energy metabolism to support the highly energy‐dependent protein synthesis machinery is poorly understood. Methods: Here, we used myotubes derived from primary culture of mouse myoblasts to study the effect of citrulline on both energy metabolism and protein synthesis under different limiting conditions. Results: When serum/amino acid deficiency or energy stress (mild uncoupling) were applied, citrulline stimulated muscle protein synthesis by +22% and +11%, respectively. Importantly, this increase was not associated with enhanced energy status (ATP/ADP ratio) or mitochondrial respiration. We further analysed the share of mitochondrial respiration and thus of generated ATP allocated to different metabolic pathways by using specific inhibitors. Our results indicate that addition of citrulline allocated an increased share of mitochondrially generated ATP to the protein synthesis machinery under conditions of both serum/amino acid deficiency (+28%) and energy stress (+21%). This reallocation was not because of reduced ATP supply to DNA synthesis or activities of sodium and calcium cycling ion pumps. Conclusions: Under certain stress conditions, citrulline increases muscle protein synthesis by specifically reallocating mitochondrial fuel to the protein synthesis machinery. Because ATP/ADP ratios and thus Gibbs free energy of ATP hydrolysis remained globally constant, this reallocation may be linked to decreased activation energies of one or several ATP (and GTP)‐consuming reactions involved in muscle protein synthesis.